Safety and Immunogenicity of Malaria Vectored Vaccines Given with Routine Expanded Program on Immunization Vaccines in Gambian Infants and Neonates: A Randomized Controlled Trial - Mensah, Victorine A.; Roetynck, Sophie; Kanteh, Ebrima K.; Bowyer, Georgina; Ndaw, Amy; Oko, Francis; Bliss, Carly M.; Jagne, Ya Jankey; Cortese, Riccardo; Nicosia, Alfredo; Roberts, Rachel; D’Alessio, Flavia; et al. (Frontiers in Immunology, 2017)
Background Heterologous prime-boost vaccination with ChAd63 and MVA encoding ME-TRAP has shown acceptable safety and promising immunogenicity in African adult and pediatric populations. If licensed, this vaccine could be given to infants receiving routine childhood immunizations. We therefore evaluated responses to ChAd63 MVA ME-TRAP when co-administered with routine Expanded Programme on Immunization (EPI) vaccines. Methods We enrolled 65 Gambian infants and neonates, aged sixteen, eight or one week at first vaccination and randomized them to receive either ME-TRAP and EPI vaccines or EPI vaccines only. Safety was assessed by the description of vaccine-related adverse events. Immunogenicity was evaluated using IFNγ ELISpot, whole-blood flow cytometry and anti-TRAP IgG ELISA. Serology was performed to confirm all infants achieved protective titers to EPI vaccines. Results The vaccines were well tolerated in all age groups with no vaccine-related serious adverse events. High-level TRAP specific IgG and T cell responses were generated after boosting with MVA. CD8+ T cell responses, previously found to correlate with protection, were induced in all groups. Antibody responses to EPI vaccines were not altered significantly. Conclusion Malaria vectored prime-boost vaccines co-administered with routine childhood immunizations were well tolerated. Potent humoral and cellular immunity induced by ChAd63 MVA ME-TRAP did not reduce the immunogenicity of co-administered EPI vaccines, supporting further evaluation of this regimen in infant populations. Trial registration The clinical trial was registered on Clinicaltrials.gov (NCT02083887) and the Pan-African Clinical Trials Registry (PACTR201402000749217).